Nutrição mineral e produtividade de pimentão (Capsicum annuum L.) em resposta a diferentes biofertilizantes líquidos no solo - Alves, Gibran da Silva (2006)
Green bell pepper (Capsicum annuum L.) is a tropical plant of the Solanaceae family with origin in Latin America. In recent years, organic cropping systems using liquid biofertilizers have had an important impulse in Brazil. The objectives of this study were to evaluate green bell pepper yield, soil fertility changes and plant nutritional status in response to different types of liquid biofertilizers applied to the soil. The experiment was carried out at Macaquinhos Farm, in the municipality of Remígio-PB, in a randomized block design with three replicates. Treatments were distributed on a 2 × 5 factorial arrangement, regarding two types of cattle manure biofertilizer (raw and agrobio) and five doses of biofertilizers based on calcium rates (0; 0,65; 1,30; 1,95 and 2,60 g pit-1). Each plot was composed by 21 pits spaced by 1 × 0,50 m, with two plants. The use of biofertilizers in the doses tested in this study had no significant effect on green bell pepper growth as measured by height and stem diameter. For average fruit mass and average number of fruits per pit, there was a significant response green bell pepper plants to the calcium doses, regardless the type of biofertilizer. A statistical superiority of agrobio biofertilizer over raw biofertilizer was detected for the levels of sulfur, boron, iron and zinc in plant leaf tissues. Regarding soil fertility components, there was no difference between the two biofertilizer types, but pH values and phosphorus and potassium levels increased significantly.